Potential of solar thermal collector combined with dual phase change materials for different energy demands: An energy, economic, and environmental assessment - Chopra K.; Tyagi V.V.; Enosh R.B.; Kumawat P.; Pandey P.; Kumar D.; Mansor M.; Rajamony R.K.; Pandey A.K. (Elsevier Ltd, 2025)
In this study, three different types of solar thermal systems i.e. ETSC-A (lauric acid integrated with a hot water tank), ETSC-B (lauric acid integrated with hot water tank and palmitic acid with evacuated tube), and ETSC-Conv (without phase change materials) have been designed and fabricated. The energy performance of ETSC-A and ETSC-B compared to ETSC-Conv was found to be 30.94, 45.37, & 49.27 %, and 48.37, 76.36, & 57.88 % higher for ED-I, ED-II, and ED-III respectively. Concerning, techno-economic analysis, values of LCWH, NPV, and PBP for ETSC-B and ETSC-A in comparison to ETSC-Conv are found to be higher by 24.41 %, 26.44 % & 36.51 and 22 %, 24.36 % & 31.91 % respectively. About environmental scan, ETSC-B, and ETSC-A can mitigate more CO2 and generate revenue by almost 60 % and 41 % respectively than ETSC-Conv. The commercial deployment of developed systems specifically ETSC-B is not only advantageous in terms of thermal performance and economic viewpoint but also mitigates carbon dioxide emission. ? 2024 Elsevier Ltd